What Students Are Telling Us: A Case Study on EFL Needs and Perceptions in the Classroom - Bailey, Angela C (Íkala, Revista de Lenguaje y Cultura, 2017)
The purpose of this study was to analyze questionnaires about students’ language learning beliefs in Barranquilla, Colombia. This qualitative, interpretative case study stems from the convergence of three research areas: beliefs about language learning, economic and sociocultural issues surrounding the language-learning context. Findings reveal that students’ beliefs and perceptions about language learning are fluid and constantly shifting; thus, providing a clearer idea of who Colombian language students are. Implications demonstrate that by addressing these shifts of beliefs and perceptions in our classroom practices, teachers could invariably make English language learning more interesting, context specific, and relevant to students.